Trade Openness, Renewable Energy, and Environmental Quality: The Role of Infrastructure in Developed and Developing Countries - Hakimi, Abdelaziz; Saidi, Hichem (International Journal of Energy Economics and Policy, 2025)
This study examines the relationship between trade openness, renewable energy, and environmental quality, with a specific focus on the role of infrastructure in developed and developing countries. To address this objective, we employ a comprehensive panel dataset covering 154 countries over the period 1990 to 2024. To account for heterogeneity across different stages of development, the full sample was divided into 112 developing countries and 42 developed countries, enabling a comparative analysis of the dynamics across contexts. We perform the two-step System Generalized Method of Moments (SGMM) estimator, which effectively addresses potential endogeneity, unobserved heterogeneity, and dynamic relationships among the variables. The findings provide insights that trade openness significantly increases the CO2 emission; renewable energy significantly enhances the environmental quality, while the effect of infrastructure differs across samples. We also found that infrastructure moderates both the trade-CO2 emission and renewable energy- CO2 emissions relationships. Countries in the full sample and developing countries benefit from an interaction between trade, renewable, and infrastructure. These interactional relationships significantly decrease CO2 emissions. Overall, this study contributes to the understanding of the trade–energy–infrastructure-environment nexus and offers policy implications for designing sustainable development strategies tailored to diverse national contexts.